1987
DOI: 10.5962/bhl.title.100219
|View full text |Cite
|
Sign up to set email alerts
|

Guide to understory burning in ponderosa pine-larch-fir forests in the Intermountain West

Abstract: Harrington, Michael G. Stand, fuel and potential fire behavior characteristics in an irregular southwestern Arizona ponderosa pine stand. Research Note RM-418. Fort Collins, CO: U.S. Department of Agriculture, Forest Service, Rocky Mountain Forest and Range Experiment Station; 1982.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…No evidence was found for extensive crown fires, but individual trees and groups of trees of about 0.5 ha were killed. Kilgore (1971) noted that fire in red fir dominated stands had little effect on the species composition and stand structure. He observed that little crowning took place in these fires, and although many red fir seedlings and saplings were killed, few older red fir were affected.…”
Section: Studymentioning
confidence: 99%
See 4 more Smart Citations
“…No evidence was found for extensive crown fires, but individual trees and groups of trees of about 0.5 ha were killed. Kilgore (1971) noted that fire in red fir dominated stands had little effect on the species composition and stand structure. He observed that little crowning took place in these fires, and although many red fir seedlings and saplings were killed, few older red fir were affected.…”
Section: Studymentioning
confidence: 99%
“…12). Kilgore (1971) reports a fire in the upper montane that was suppressed at 1 ⁄4 acre in 1968, but he indicates the fire would have had little impact and probably would have gone out at a small acreage even if it had not been suppressed. He reports another that burned 2 months and covered less than 2 acres.…”
Section: Studymentioning
confidence: 99%
See 3 more Smart Citations